PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DALAM MENDUKUNG KINERJA PENGADILAN TINGGI AGAMA PONTIANAK - B51110105, Juniati (Jurnal KIAFE, 2013)
Responsibility accounting is a system that measures the results achieved by each responsibility center according to the information needed to operate the central leaders to account. In the neighborhood of the Supreme Court of the Republic of Indonesia, especially in the Pengadilan Tinggi Agama Pontianak has two responsibility centers are cost centers and revenue centers, but to know the performance of Pengadilan Tinggi Agama Pontianak related to the administration of justice religion of the early cases go up to the decided cases it is more focused on the central revenue due to income received (costs registers case) from the litigants for settlement of the case and can only be recognized/paid if the case had been dropped. Thus the title of this research is "Application of Responsibility Accounting Performance Pengadilan Tinggi Agama Pontianak". The problem in this research is to discuss how the application of responsibility accounting in supporting the performance of High Religious Court Pontianak. The purpose of the study is to examine the application of responsibility accounting in supporting the performance of Pengadilan Tinggi Agama Pontianak. The research method uses a qualitative research approach descriptive method is a method that provides an overview as well as a state of facts and objects that exist in the field of research to solve problems and see to what extent the application of responsibility accounting in supporting the performance of Pengadilan Tinggi Agama Pontianak. The results and discussion of the application of responsibility accounting in supporting the performance of Pengadilan Tinggi Agama Pontianak is as follows: the application of responsibility accounting in supporting the performance of Pengadilan Tinggi Agama Pontianak is good, based on evaluation of the organizational structure and evaluation questionnaires in Pengadilan Tinggi Agama Pontianak. As for the suggestions proposed by the authors of this research that should further improve the oversight of the implementation of the resolution and case management, as well as the main task/function of each unit that has been created in order to be implemented in an optimal and adequate.